The Influence of NCT 127 Brand Ambassador on The “Click” Toothpaste Brand Image in NCTzen - Kamila Alfiana Rahme; Serafine Angelina Yudianto; Eugenia Desta Riana Putri; Muhamad Nastain (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
Toothpaste is one of the primary needs of the community, which means that the community needs its supply. As a dental health product, the type of toothpaste also has a significant influence, not only on dental health but also on fresh breath. Several companies with well-known toothpaste brands always try to promote their products in various ways. Through television and advertisements, like toothpaste